2018
DOI: 10.1016/j.apor.2018.08.013
|View full text |Cite
|
Sign up to set email alerts
|

A review on predicting critical collapse pressure of flexible risers for ultra-deep oil and gas production

Abstract: Flexible riser is a key enabler for the oil and gas production in ultra-deep water which transports production fluids between floating production systems and subsea wells. As oil and production heads to water depths in excess of 3000 m, high hydrostatic pressure has been one primary challenge facing the riser operators. Excessive hydrostatic pressure may cause collapse failure of flexible risers and thus predicting the critical collapse pressure is of significant importance to their anti-collapse design. Colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 52 publications
(71 reference statements)
0
10
0
Order By: Relevance
“…Since marine risers are tubular structures with varied segments, the experimental tests on composite risers were conducted at microscale levels (on composite materials) [257][258][259] and at macroscale levels (on composite risers with composite tubes) [47,80,307,308], which are benchmarked against those of marine steel risers, such as steel catenary risers [35,286]. It is also crucial to test the failure in risers, as research on carbon-fibre-reinforced composite risers have revealed failure mechanisms [59][60][61][62][63] linked to various loading scenarios [131,134,187,195]. Previous experimental studies on composite risers were based on scale-dependent methods of analysis, as tabulated in Table 6.…”
Section: Experimental Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since marine risers are tubular structures with varied segments, the experimental tests on composite risers were conducted at microscale levels (on composite materials) [257][258][259] and at macroscale levels (on composite risers with composite tubes) [47,80,307,308], which are benchmarked against those of marine steel risers, such as steel catenary risers [35,286]. It is also crucial to test the failure in risers, as research on carbon-fibre-reinforced composite risers have revealed failure mechanisms [59][60][61][62][63] linked to various loading scenarios [131,134,187,195]. Previous experimental studies on composite risers were based on scale-dependent methods of analysis, as tabulated in Table 6.…”
Section: Experimental Testsmentioning
confidence: 99%
“…However, risers are affected by vibrations and thus require tensioners designed for the control of marine risers [56][57][58]. Different failure modes have also been recorded on marine risers [59][60][61][62][63][64]. Additional riser functions, depending on the application, include: conveying fluids between the wells and the floating, production and storage (FPS) units.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the computational cost, simplified FE models were developed as an alternative strategy (Li et al 2018). One common simplification is to replace the self-interlocking layers with equivalent tubes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a number of studies have focused on the mechanical behavior of flexible pipe, such as the instability of the armor wire [17], the collapse of the carcass layers [18], and fatigue reliability analysis [19]. Although the sealing behavior of the end fitting is unlike the mechanical behavior of the flexible pipe body or the layers inside the end fitting, which have been extensively investigated [8,20], there has been relatively little research on the sealing performance of the end fittings themselves.…”
Section: Introductionmentioning
confidence: 99%